Annamária-Izabella Pázsint, Prosopographia Ponti Euxini. Callatis et Odessus, Cluj-Napoca, Mega Publishing House, 2024, 308 p. ISBN 978-606-020-707-8 - Roxana-Gabriela CURCĂ (Journal of Ancient History and Archaeology)
Review: Annamária-Izabella Pázsint, Prosopographia Ponti Euxini. Callatis et Odessus, Cluj-Napoca, Mega Publishing House, 2024, 308 p. ISBN: 978–606-020–707–8.